PEWARISAN TARI PIRING LAMPU TOGOK DALAM MASYARAKAT GURUN BAGAN LUBUAK SIKARAH KOTA SOLOK - Megawati Megawati; Idawati Syarif; Susmiarti Susmiarti (SENDRATASIK UNP, 2012)
This type of research is a qualitative descriptive method. Data was collected through observation, interviews, and literature. Object of this study is Togok Desert Dance Chart Plate Lamp, Lubuk Sikarah. The findings of the studies of inheritance Dance Togok Plate Lamp In Desert Peoples Chart, Lubuk Sikarah, Solok City. In getting results. Inheritance system, there are inherit inheritance seperguruan dance, music, costumes, properties Togok Plate Lamp. the dance bequeath togok plate lights there are several requirements that must be passed by students who want to learn, the students also participate in various conditions presented by dance teachers, learn through the examples given by the teacher after which students mimic the movements made by the teacher, then students practice under the next teacher students practice independently.